A study to Assess the Knowledge Regarding Gestational Diabetes Mellitus among Pregnant Mothers and Self Care Practice of Gestational Diabetes Mellitus Management among Mothers with Diabetes in Pregnancy Attending Selected Hospitals of Kottayam District (Medico Legal Update, 2021)
The study was conducted to assess thethe knowledge regardingGestational Diabetes Mellitus amongpregnant mothers and self care practice of Gestational Diabetes Mellitus management among mothers withdiabetes in pregnancy attending selected hospitals of Kottayam District. The objectives were to assess thelevel of knowledge regarding Gestational Diabetes Mellitus among pregnant mothers, to assess the self carepractice of Gestational Diabetes Mellitus management among mothers with diabetes in pregnancy, to findassociation between level of knowledge regarding Gestational Diabetes Mellitus and selected demographicvariables,to find correlation between knowledge and self care practice of Gestational Diabetes Mellitusmanagement among mothers with diabetes in pregnancy. The research design used in the present study isnon experimental descriptive design. The study was conducted among 60 antenatal mothers and 15 motherswith gestational diabetes mellitus by using non probability convenient sampling technique.In the presentstudy it was found that 33.3%mothers had poor knowledge, 33.3% had average knowledge and 33.3% hadgood knowledge regarding Gestational diabetes mellitus.When comes to practice t 46.7% had satisfactorypractices and 53.3% had good practice. There is a positive correlation between knowledge and practice(p=0.04).